Analysis of the Effectiveness of Hydrogel Based on Patikan Kebo Leaf Extract and Honey in Therapy of II Degree Burns - Winda Puji Lestari Roro; Khorinnisa Hayatul; Nurtiara Alma; Lita Septiana Enggel; Yuliyanti Dwi; Nur Handayani Santi (E3S Web of Conferences)
Treatment of burns such as using toothpaste, butter, oil, and ice is less effective in treating burns. A safer and more effective alternative is needed as a dressing for burn wounds. The use of burn wound coverings with the moist wound healing principle is recommended because they are flexible, elastic, and support the burn wound healing process. Patikan kebo leaves contain flavonoids, tannins, alkaloids, saponins, and terpenoids which function as antibacterial and anti-inflammatory in the healing process of second-degree burns. This research aims to make a hydrogel from patikan kebo leaf extract with honey and tests its antibacterial and anti-inflammatory effectiveness as a treatment for second-degree burns. The method used is synthesis hydrogel, antibacterial and anti-inflammatory tests, and continued testing using histopathology tests. The antibacterial test results showed that the extract didn’t show better activity than the positive control on Escherichia coli bacteria, while the F4 sample showed the best antibacterial effect on Streptococcus aureus bacteria. Anti-inflammatory and burn healing test seen from the results of histopathology tests produced the best percentage of burn wound healing in sample F4.